4D-flow cardiac magnetic resonance imaging after aortic root replacement with long-valved decellularized aortic homografts: comparison to valve-sparing aortic root replacement and healthy controls. (25th January 2022) - Cvitkovic, Tomislav; Bobylev, Dmitry; Horke, Alexander; Avsar, Murat; Beerbaum, Philipp; Martens, Andreas; Böthig, Dietmar; Petenà, Elena; Gutberlet, Marcel; Beyer, Frerk Hinnerk; Wacker, Frank; Cebotari, Serghei; et al.
Abstract: OBJECTIVES: Long-valved decellularized aortic homografts (DAH) may be used in young patients to treat aortic valve disease associated with aortic root dilatation, thereby eliminating the need for prosthetic material and anticoagulation. METHODS: Thirty-three male subjects in 3 equally sized cohorts were compared: patients following DAH implantation with a median age of 29 years [interquartile range (IQR) 27.5–37.5], patients post-valve-sparing aortic root replacement (VSARR), median 44 years (IQR 31.5–49) and healthy controls, median 33 years (IQR 28–40, P = 0.228). Time-resolved three-dimensional phase-contrast cardiac magnetic resonance imaging was performed to assess maximum blood flow velocity, pulse wave velocity, mechanical energy loss (EL), wall shear stress and flow patterns (vorticity, eccentricity, helicity) in 5 different planes of the aorta. RESULTS: The mean time between surgery and cardiovascular magnetic resonance was 2.56 ± 2.0 years in DAH vs 2.67 ± 2.1 in VSARR, P = 0.500. No significant differences in maximum velocity and pulse wave velocity were found between healthy controls and DAH across all planes. Velocity in the proximal aorta was significantly higher in VSARR (182.91 ± 53.91 cm/s, P = 0.032) compared with healthy controls. EL was significantly higher in VSARR in the proximal aorta with 1.85 mW (IQR 1.39–2.95) compared with healthy controls, 1.06 mW (0.91–1.22, P = 0.016), as well as in the entire thoracic aorta. In contrast, there was no significant EL in DAH in the proximal, 1.27 m/W (0.92–1.53, P = 0.296), as well as in the thoracic aorta, 7.7 m/W (5.25–9.90, P = 0.114), compared with healthy controls. There were no significant differences in wall shear stress parameters for all 5 regions of the thoracic aorta between the 3 groups. DAH patients, however, showed more vorticity, helicity and eccentricity in the ascending aorta compared with healthy controls ( P < 0.019). CONCLUSIONS: Decellularized long aortic homografts exhibit near to normal haemodynamic parameters 2.5 years postoperatively compared with healthy controls and VSARR. Abstract : Limited surgical options are available for aortic valve pathology associated with ascending aortic dilatation.